From Family to School: Dual Protection from Fathers and Teachers for Children’s Mental Health - Ellen Prima (unprimdn.ac.id, 2026)
Mental health in children is a critical issue that requires specialized attention, particularly during the preschool years. This study investigates the negative impact of maternal authoritarian parenting on the social-emotional development of preschoolers, specifically examining the mediating role of emotion regulation and the moderating effects of father-child and teacher-child relationships. Involving 412 preschoolers from kindergartens in Purwokerto, along with their parents and teachers, the research utilized a longitudinal design with a six-month interval. Data were analyzed using Polynomial Curved Surface Fitting (PCSF) to validate a double moderative mediation model. The results indicate that maternal authoritarian parenting significantly reduces children’s emotion regulation (β = -.211, p < .001), which in turn correlates with mental health issues (r = -.175, p < .01). However, positive relationships with fathers (β = .163, p < .05) and teachers (β = .145, p < .001) act as synergistic protective factors that buffer these adverse effects. These findings offer strategic implications for educational interventions and policies aimed at safeguarding early childhood psychological well-being.